2016
DOI: 10.1103/physrevd.93.026010
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and mutual information in two-dimensional nonrelativistic field theories

Abstract: We carry out a systematic study of entanglement entropy in nonrelativistic conformal field theories via holographic techniques. After a discussion of recent results concerning Galilean conformal field theories, we deduce a novel expression for the entanglement entropy of (1+1)-dimensional Lifshitz field theories -this is done both at zero and finite temperature. Based on these results, we pose a conjecture for the anomaly coefficient of a Lifshitz field theory dual to new massive gravity. It is found that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…In this background, we will prove the existence of a new entangling surface by deforming the geodesic. Consequently, we establish that the existent analysis in this regard [20] requires further attentions. As a final example, in section 5 we investigate the deformation of the entangling surface for the Warped AdS 3 spacetime.…”
Section: Jhep09(2016)144mentioning
confidence: 73%
See 2 more Smart Citations
“…In this background, we will prove the existence of a new entangling surface by deforming the geodesic. Consequently, we establish that the existent analysis in this regard [20] requires further attentions. As a final example, in section 5 we investigate the deformation of the entangling surface for the Warped AdS 3 spacetime.…”
Section: Jhep09(2016)144mentioning
confidence: 73%
“…Moreover, in [17] the authors have shown that, for a particular class of asymptotically AdS spacetimes in four dimensional higher derivative theory, a perturbative modification of AdS geodesic provides the correct entangling surface satisfying the necessary physical boundary conditions. Further analysis in this context can be found in [18][19][20].…”
Section: Jhep09(2016)144mentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the case of non-static states the dynamical exponent may appear in the entanglement entropy (see [52,53]). 7,8 7 Also in the case of higher derivative gravity theories, appearance of the dynamical critical exponent in the entanglement entropy was previously reported in [54,55]. 8 See also [56] for related studies in hyperscaling violating backgrounds with momentum relaxation.…”
Section: Jhep10(2016)135mentioning
confidence: 74%
“…This constructs the very most literature of quantum entanglement in the context of QFTs. Although there have been some attempts so far to analyse the entanglement structure in the non-relativistic cases with z = 1 (see [15][16][17] on the QFT side and [18][19][20][21][22][23] in the context of gauge/gravity duality 1 ), still there are several open questions about the role of z in the entanglement structure of such theories.…”
Section: Jhep07(2017)120mentioning
confidence: 99%